2023
DOI: 10.1101/2023.03.21.533618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microsaccades track location-based object rehearsal in visual working memory

Abstract: Besides controlling eye movements, the brain's oculomotor system has been implicated in the control of covert spatial attention and the rehearsal of spatial information in working memory. We investigated whether the oculomotor system also contributes to rehearsing visual objects in working memory when object location is never asked about. To address this, we tracked the incidental use of locations for mnemonic rehearsal via directional biases in microsaccades while participants maintained two visual objects (c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…A looking at nothing effect was also observed in studies investigating how internal attention selects information from the visuospatial working memory (Linde-Domingo & Spitzer, 2023; B. Liu et al, 2022;Sahan et al, 2023, van Ede et al, 2019, 2021Vries & van Ede, 2024). Selective attention operates in a similar manner over external and internal information (e.g., Awh & Jonides, 2001;Griffin & Nobre, 2003;van Ede & Nobre, 2023;Verschooren & Egner, 2023;Zhou et al, 2022), which can also be observed in eye movements (Theeuwes et al, 2009).…”
Section: Imagery Associated With Visuospatial Memorymentioning
confidence: 67%
See 1 more Smart Citation
“…A looking at nothing effect was also observed in studies investigating how internal attention selects information from the visuospatial working memory (Linde-Domingo & Spitzer, 2023; B. Liu et al, 2022;Sahan et al, 2023, van Ede et al, 2019, 2021Vries & van Ede, 2024). Selective attention operates in a similar manner over external and internal information (e.g., Awh & Jonides, 2001;Griffin & Nobre, 2003;van Ede & Nobre, 2023;Verschooren & Egner, 2023;Zhou et al, 2022), which can also be observed in eye movements (Theeuwes et al, 2009).…”
Section: Imagery Associated With Visuospatial Memorymentioning
confidence: 67%
“…Various studies exploring internal attention shifts in the domain of visuospatial memory have consistently observed a gaze bias towards the location of an internal representation; however, they failed to demonstrate a clear functional impact on memory performance (B. Liu et al, 2022;van Ede et al, 2019;Vries & van Ede, 2024;Walcher et al, 2023b). This suggests that while internal coupling reflects the underlying cognitive processes, it may not directly enhance the effectiveness of internal selection.…”
Section: Internal Coupling As a Marker Of Internal Attention Shiftsmentioning
confidence: 99%
“…Traditional encoding and recall paradigms, frequently used to investigate internal coupling, rely on a sequence where information is presented visually and later retrieved (De Vries & Van Ede, 2023;Mast & Kosslyn, 2002;Spivey & Geng, 2001). In such paradigms, eye movements could be associated with the original position of the encoded memory content and co-activated when retrieving the memory content (e.g., Mast & Kosslyn, 2002;Spivey & Geng, 2001).…”
Section: The Present Studymentioning
confidence: 99%
“…From studies with 2D displays—in which the spatial relation between memoranda and observer remains fixed ( Figure 1 a)—the role of space is well established. Space serves as a scaffold for working memory retention ( de Vries & van Ede, 2023 ; Heuer & Rolfs, 2021a ; Jiang, Olson, & Chun, 2000 ; Pertzov & Husain, 2014 ; Schneegans & Bays, 2017 ), as well as for the selection and prioritization of specific objects within working memory ( Griffin & Nobre, 2003 ; Heuer & Rolfs, 2021a ; Kuo, Rao, Lepsien, & Nobre, 2009 ; van Ede, Chekroud, & Nobre, 2019 ). One particular and recent demonstration of this involves spatial biases in gaze when selectively attending to objects in visual working memory ( de Vries, Fejer, & van Ede, 2023 ; Draschkow, Kallmayer, & Nobre, 2022 ; van Ede, Board, & Nobre, 2020 ; van Ede, Chekroud, & Nobre, 2019 ; van Ede, Deden, & Nobre, 2021 ) in the absence of anything to look at (see also Ferreira, Apel, & Henderson, 2008 ; Martarelli, Ovalle Fresa, Popic, Globig, & Rothen, 2022 ; Spivey & Geng, 2001 ; Wynn, Shen, & Ryan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%